Peak nasal inspiratory flow: normal values in a healthy vietnamese adult population - Hoang , Phuoc Minh; Ho , Dang An (Tạp chí Y Dược Huế, 2025)
Background: Peak nasal inspiratory flow (PNIF) is an objective measurement of nasal patency. However, standard reference values specific to the Vietnamese population have not been established. Materials and methods: In a cross-sectional study, PNIF was measured three times in 300 healthy Vietnamese participants aged 17 to 88. Normal PNIF values for males and females were determined through multiple regression analysis, adjusting for age and height. Results: Males showed significantly higher PNIF values than females (158.78 ± 40.97 vs. 113.40 ± 31.93 L/min, p < 0.001). Both age and height were found to significantly influence PNIF (p < 0.001). After adjusting for these variables, the average difference between genders was 33.82 ± 33.71 L/min. The reference range for males was 121.93 (95% CI: 119.16 - 124.69) to 181.68 (95% CI: 178.92 - 184.45) L/min, and for females, it was 92.53 (95% CI: 90.62 - 94.43) to 143.44 (95% CI: 141.54 - 145.34) L/ min. The third PNIF measurement yielded the highest average, which was statistically significantly different from the first and second attempts. Conclusions: PNIF is influenced by gender, age, and height. This study provides reference PNIF values for healthy Vietnamese adults, adjusted for these factors.